Complex dependence on the elastically active chains density of the strain induced crystallization of vulcanized natural rubbers, from low to high strain rate. (5th August 2016) - Candau, Nicolas; Chazeau, Laurent; Chenal, Jean-Marc; Gauthier, Catherine; Munch, Etienne
Abstract: Strain Induced Crystallization (SIC) of Natural Rubbers (NR) with different network chain densities ( ν ) is studied. For the weakly vulcanized rubber, the melting stretching ratio λm at room temperature is the lowest. This is correlated with larger crystallites in this material measured by in situ WAXS, suggesting their higher thermal stability. SIC kinetics is then studied via stretching at various strain rates (from 5.6 × 10 −5 s −1 up to 2.8 × 10 1 s −1 ). For the slowest strain rates, SIC onset ( λ c ) is clearly the lowest in weakly vulcanized rubber. By increasing the strain rate, λ c of the different materials increase and converge. For the highest strain rates, λc values still increase but less rapidly for the weakly vulcanized sample. This complex dependence on the elastically active chains (EAC) density of SIC has been confirmed by in situ WAXS during dynamic experiments and interpreted as a consequence of both the polymer chain network topology and of the entanglements dynamics. Graphical abstract: Highlights: SIC of natural rubbers with different network chain densities is studied. Crystallites have the higher thermal stability in the weakly vulcanized rubber. At high strain rates, crystallization is eased in the weakly vulcanized rubber. Such behaviour is explained by network chain topology and entanglements dynamics.